2007
DOI: 10.1007/s10164-007-0057-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of predation risk on mating behavior of the Kanzawa spider mite

Abstract: In the Kanzawa spider mite, Tetranychus kanzawai, adult males locate pre-reproductive quiescent females and engage in precopulatory mate guarding. We found that re-reproductive quiescent females preferred to be near veins, rather than other leaf parts, and moreover, adult males spent more time along the vein than on other parts. Consequently, T. kanzawai males found more quiescent females along veins than those on other parts. However, the predatory mite Neoseiulus womersleyi also found more quiescent T. kanza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
(9 reference statements)
0
8
0
Order By: Relevance
“…To clarify this possibility, future studies should examine whether mounting is more costly to T. kanzawai males than attending behavior. Oku and Yano (2008) observed only mounting behavior as precopulatory mate guarding; however, most of T. kanzawai adult males guarded quiescent females. One reason for this result may be that in their experiments, Oku and Yano (2008) kept more than 50 males on the same leaf disc until they were used.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To clarify this possibility, future studies should examine whether mounting is more costly to T. kanzawai males than attending behavior. Oku and Yano (2008) observed only mounting behavior as precopulatory mate guarding; however, most of T. kanzawai adult males guarded quiescent females. One reason for this result may be that in their experiments, Oku and Yano (2008) kept more than 50 males on the same leaf disc until they were used.…”
Section: Discussionmentioning
confidence: 99%
“…Contact mate guarding is more effective in ensuring the reproductive success of males than non-contact mate guarding (e.g., Singer 1987;Convey 1989). However, contact mate guarding is sometimes energetically costly to males (Plaistow et al 2003;Saeki et al 2005;Sparkes et al 1996) and conspicuous to predators (Zeiss et al 1999;Cothran 2004;Oku and Yano 2008). Therefore, in species which use both contact and non-contact mate guarding, it is expected that males should change mate guarding behavior in response to their circumstances.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, several predator cues alter mating tactics in male wolf spiders 575 studies have demonstrated that males differentially use mating tactics based upon the detection of predators or perceived risk of predatory eavesdroppers (Endler, 1987;Reynolds et al, 1993;Godin, 1995;Oku & Yano, 2008); and that males adopting less conspicuous mating tactics experience lower predation risk (Cade, 1979;Howard, 1984;Larison, 2007). We explore whether predation costs associated with predatory eavesdropping heterospecifics could influence mating tactic expression in the wolf spider Rabidosa punctulata.…”
Section: Introductionmentioning
confidence: 99%